2018
DOI: 10.1177/1753193418801280
|View full text |Cite
|
Sign up to set email alerts
|

Classification of congenital upper limb anomalies: towards improved communication, diagnosis, and discovery

Abstract: Recently the International Federation of Societies for Surgery of the Hand replaced the Swanson scheme for classifying congenital upper limb anomalies with the Oberg, Manske, Tonkin (OMT) classification. This review explores the reasons for this change after nearly 50 years of using the Swanson classification. In particular, it documents the state of our understanding regarding genetics and limb development at the time Swanson generated his classification. It also describes the continued progress in clinical g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 84 publications
(92 reference statements)
0
11
0
3
Order By: Relevance
“…Congenital limb defects may be classified according to the axis defect. For example, brachydactyly and amelia are related to defects in the proximodistal axis; polydactyly as well as radial/ulnar ray deficiencies are related to defects in the anteroposterior axis; and ventral/dorsal dimelia (the appearance of palmar structures on the dorsal aspect of the hand and the appearance of dorsal structures on the ventral aspect of the hand, respectively) are related to defects in the dorsoventral axis [53, 54]. Hence, it would be pertinent to understand the origin of syndactyly with respect to the developmental axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Congenital limb defects may be classified according to the axis defect. For example, brachydactyly and amelia are related to defects in the proximodistal axis; polydactyly as well as radial/ulnar ray deficiencies are related to defects in the anteroposterior axis; and ventral/dorsal dimelia (the appearance of palmar structures on the dorsal aspect of the hand and the appearance of dorsal structures on the ventral aspect of the hand, respectively) are related to defects in the dorsoventral axis [53, 54]. Hence, it would be pertinent to understand the origin of syndactyly with respect to the developmental axis.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it would be pertinent to understand the origin of syndactyly with respect to the developmental axis. Oberg [53] studied this extensively and concluded that syndactyly is best classified under malformations of “unspecified” axis [53]. However, since FGF8 is the key middle step mediating the pathogenesis of syndactyly, one may argue that syndactyly may be considered as a defect in the proximodistal axis (FGF8 is the main controller of this axis).…”
Section: Discussionmentioning
confidence: 99%
“…Sie berücksichtigt neuere genetische und entwicklungsbiologische Erkenntnisse der Extremitätenausbildung. Durch ihre Unterteilung in Malformationen, Deformationen und Dysplasien sowie Syndrome bildet sie die Pathogenese von Fehlbildungen besser ab als die früher verwendete Swanson-Klassifikation [3]. Für den klinischen Gebrauch ist sie jedoch zu kompliziert.…”
Section: Klassifikationunclassified
“…12 Recientemente, se describió una clasificación de anomalías congénitas de miembro superior llamada Oberg, Manske, Tonkin (OMT), la cual pretende dar una explicación genética y una clasificación etiológica más completa que la de Swanson o Bell y, de esta manera, generar una comunicación global e interdisciplinaria. 13 La paciente no tenía ninguna de las condiciones etiológicas antes mencionadas; no obstante, es importante mencionar el antecedente de las deformidades en las falanges, así como la rizartrosis importante que presenta en ambas manos, la cual es la etiología más probable de ambas rupturas.…”
Section: Wwwmedigraphicorgmxunclassified